Liquid Metal‐Conductive Thermoplastic Elastomer Integration for Low‐Voltage Stiffness Tuning. Issue 12 (12th October 2017) - Rich, Steven; Jang, Sung‐Hwan; Park, Yong‐Lae; Majidi, Carmel
Abstract: An electrically responsive composite is introduced that exhibits muscle‐like changes in elastic stiffness (≈1–10 MPa) when stimulated with moderate voltages (5–20 V). The stiffness‐tuning element contains an embedded layer of conductive thermoplastic elastomer (cTPE), composed of a propylene–ethylene copolymer and a percolating network of carbon black. Two opposite surfaces of the cTPE layer are coated with a ≈20 µm thin film eutectic gallium–indium (EGaIn) liquid metal alloy. When a voltage is applied to these EGaIn electrodes, electric current passes through the cTPE. This causes internal Joule heating, which induces a phase transition that changes the composite from its stiff state ( E = 10.4 MPa) to its compliant state ( E = 0.7 MPa). Differential scanning calorimetry is performed to show that this state change is governed by a solid–liquid transition. Voltage‐dependent activation times are demonstrated that can be reduced to below 2 s and show the ability of the composite to recover its original shape after large strains. To illustrate its applicability in robotics, the composite is incorporated into an underactuated robotic finger, providing it with two different bending modes. The ability to use the composite as a moldable stiffness‐tuning splint is also demonstrated. Abstract : The ability to quickly and reversibly tune stiffness is important for many soft robotic and biomedical applications. This work incorporates liquid metal and conductive thermoplastic elastomers to create electrically activated stiffness‐tuning actuators for use in a robotic finger and a remoldable splint.